2009
DOI: 10.1177/070674370905401107
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Dominic Interactive in a Large French Sample

Abstract: The satisfactory psychometric properties of the DI along with other demonstrated advantages of this instrument (children enjoy the activity, parents approve of it, and it is cost-effective) and its cultural adaptability support the consideration of the DI for epidemiologic studies in diverse cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 33 publications
0
51
0
1
Order By: Relevance
“…There are pictures, texts and voices to illustrate the abstract emotional and behavioral content of mental health problems and to simply the scenario for a child in primary school. Test-retest reliability and consistency studies done on the Dominic Interactive (and its cross-culture derivatives [15]), showed that this test was reliable (Chronbach’s alpha values in between 0.60 and 0.90 [16-20]). Validity studies suggest that the DI has improved validity compared with other structured interviews of young children [17].…”
Section: Methodsmentioning
confidence: 99%
“…There are pictures, texts and voices to illustrate the abstract emotional and behavioral content of mental health problems and to simply the scenario for a child in primary school. Test-retest reliability and consistency studies done on the Dominic Interactive (and its cross-culture derivatives [15]), showed that this test was reliable (Chronbach’s alpha values in between 0.60 and 0.90 [16-20]). Validity studies suggest that the DI has improved validity compared with other structured interviews of young children [17].…”
Section: Methodsmentioning
confidence: 99%
“…Lower cutpoints are one standard deviation from the mean and higher cutpoints two standard deviations above [43]. Validation studies of the DI were conducted on children aged 6-11 years and psychometric properties were found to be satisfactory with internal consistency ranging from .59 to .91 [31,43,49]. Symptom scores were used in most of our analyses and, following Linares et al [50], the percentages of children reaching the probable clinical range, based on the lower cutpoints.…”
Section: Dominic Interactivementioning
confidence: 99%
“…A yes/no format was used so that it would be easily understood by 7-year-olds. Assessments were based on the Dominique Interactif, which has been shown to have adequate reliability and validity for young children (Linares Scott, Short, Singer, Russ, & Minnes, 2006;Shojaei et al, 2009;Valla, Bergeron, Be´rube´, Gaudet, & St-Georges, 1994;Valla, Bergeron, & Smolla, 2000). Scores were z-standardized for each informant and averaged across informants to construct one overall score ( Table 1): The AGGR scale included physical, proactive, and reactive aggression (11-12 items per informant); the ADHD scale consisted of 8-9 items per informant; NAEX combined non-aggressive conduct disorder and opposition and defiance (6-9 items); ANXDEP consisted of 7-9 items.…”
Section: Dependent Variablesmentioning
confidence: 99%